CHALLENGES FACED BY THE MEMBERS OF THE FARMER PRODUCER ORGANISATIONS IN TELANGANA STATE - G. E. CH. VIDYASAGAR and A. MEENA, D. NAVYA, K. MADHU BABU, V. RAVINDER NAIK (The Journal of Research, PJTSAU, 2023)
Present study was conducted to know the challenges associated with the performance of Farmers’ Producers Organisation(FPO). Present study was conducted in Telangana state, random sampling techniques were followed in case of selecting the areaand the respondents of the present study. Data collection was done by structured interview schedule after pre-testing with thehelp of personal interview method. Henry Garett ranking technique was used to analyse the data and draw conclusion. Resultsshowed that majority of the members were facing problems with respect to irregular procurement of produce (61.29) followed byinadequate infrastructure facilities (59.92) and credit facilities are not available to the members (54.64).